2006
DOI: 10.1007/s10811-006-9128-5
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient interactions between phytoplankton and bacterioplankton under different carbon dioxide regimes

Abstract: Light, nutrients, temperature, pH, and salinity are important factors in controlling the growth of phytoplankton and bacterioplankton. Supply of key nutrients to these communities can result in mutualistic or competitive relationships between bacterioplankton and phytoplankton. In this study, we investigated growth and uptake of nutrients by the marine prasinophyte flagellate Tetraselmis chui (strain PLY429) in the presence and absence of a community of bacterioplankton at two pH levels. Growth of PLY429 and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 22 publications
(23 reference statements)
1
14
0
1
Order By: Relevance
“…Bacterial strains can also decrease ΔX max of microalgae by competing for a limiting nutrient. Such an effect has been previously reported by Meseck et al for nitrogen, and by Rhee et al and Danger et al for phosphorus [7,50,57]. Alternatively, release of toxic compounds by bacteria could also be involved in the inhibitory effect observed at the stationary phase [49,58].…”
Section: Effect Of Bacteria On Growth Of Dunaliella Spsupporting
confidence: 62%
“…Bacterial strains can also decrease ΔX max of microalgae by competing for a limiting nutrient. Such an effect has been previously reported by Meseck et al for nitrogen, and by Rhee et al and Danger et al for phosphorus [7,50,57]. Alternatively, release of toxic compounds by bacteria could also be involved in the inhibitory effect observed at the stationary phase [49,58].…”
Section: Effect Of Bacteria On Growth Of Dunaliella Spsupporting
confidence: 62%
“…The addition of single bacterial isolates to the axenic culture led to different results: Acinetobacter and Raugeria enhanced, whereas Pseudomonas reduced algal growth (Arora et al, 2012). Meseck et al (2007) studied the influence on T. chuii of the addition of a bacterial community obtained from a Tetraselmis striata culture. The bacteria strongly reduced algal growth compared with the axenic culture.…”
Section: Discussionmentioning
confidence: 99%
“…The bacteria strongly reduced algal growth compared with the axenic culture. The authors suggested competition for ammonium to be the cause of the reduced growth (Meseck et al, 2007). Park et al (2017) evaluated the effect of addition of each of the 26 bacterial isolates obtained from T. striata phycosphere to an axenic culture and studied the two isolates (Pelagibaca bermudensis and Stappia sp.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nitrification process therefore implies two negative effects in the use of microalgae for wastewater treatment: (i) the reduction of ammonium by AOB does not involve a net nitrogen reduction as it is oxidized to nitrate, which is not as easily assimilated by microalgae as ammonium [11]; (ii) the limitation of microalgae growth when the concentration of ammonium in the culture is low. In fact, Meseck et al [12] concluded that the presence of nitrifying bacteria in a microalgae culture of Tetraselmis chui reduced the specific growth rate due to their competition for nutrients. However, Risgaard-Petersen et al [13] observed that microalgae became the predominant group under non-limiting ammonium due to their higher growth rate.…”
Section: Introductionmentioning
confidence: 99%